Guerrilla marketing trends for sustainable solutions: evidence from SEM-based multivariate and conditional process approaches - Ahmed, Rizwan Raheem; Qureshi, Jawaid Ahmed; Štreimikienė, Dalia; Vveinhardt, Jolita; Soomro, Riaz Hussain (Journal of Business Economics and Management, 2020)
In today’s competitive environment, the marketing is an imperative tool for the survival and sustainable growth of any business or product. The objective of the undertaken research is to investigate the guerrilla marketing techniques for small and medium enterprises (SMEs), and their impact on consumers’ purchase decision. Researchers have also the aim to examine the impact of brand awareness and technology as mediating and moderating variables respectively in the guerrilla marketing process. A survey is undertaken by potential consumers through structured questionnaire via a quantitative method of inquiry. The data is analyzed mainly through; SEM-based structural modelling such as exploratory and confirmatory factors analysis, and conditional process analysis. The results unveil that guerrilla marketing techniques consisting of viral marketing, strange occurrences, street graphics, and memorable events have a positive and significant influence on the purchase decision. Findings of the undertaken research further demonstrated that brand awareness is a potent mediating variable that significantly enhances the influence of purchase decision, and technology played a vital role as a moderator that has a cogent impact between guerrilla marketing techniques and purchase decision of consumers. Thus, the empirical testing confirmed the importance of modified model of guerrilla marketing, which will be benefitted to both marketing practitioners and future researchers.